Chalek Juice: An alternative diet therapy of diabetes mellitus - Yunianitamara, Vinna Maulidha; Widiastuti, Erma Nurjanah; Rahayu, Cucu; Sera, Agnescia Clarissa (GHMJ (Global Health Management Journal), 2022)
Not required.